PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS DAN RISIKO BISNIS TERHADAP KEPUTUSAN EKSPANSI PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ika Wahyuni; Ida Subaida (Growth, 2021)
The purpose of this study is to determine the effect of the Liquidity, Leverage, Profitability and Business Risk variables partially or simultaneously as well as the dominant variables on the expansion decisions of property and real estate companies listed on the Indonesia Stock Exchange (IDX). The method used in this research is multiple linear regression analysis, t test, F test, dominant test and determination test. Based on the research results, it is known that the results of multiple linear regression are Y = 9.328E-17 + 0.392X1 + 0.243X2 + 0.269X3 + 0.248X4 + e. The results of the t test show that the Liquidity variable tcount 3.172 > ttable 2.014 sig 0.003 < 0.05, Leverage variable tcount 2.134 > ttable 2.014 sig 0.038 < 0.05, Profitability variable tcount 2.136 > ttable 2.014 sig 0.038 < 0.05, business risk variable tcount 2.258 > ttable 2.014 sig 0.029 < 0.05, it can be concluded that the research hypothesis (H1) which states that the variables of Liquidity, Leverage, Profitability and Business risk partially influence the decision to expand property and real estate companies listed on the Indonesia Stock Exchange (IDX). The results of the F test are known that the value of Fcount 10,416 > Ftable 2.58 sig 0.000 < 0.05, it can be concluded that the research hypothesis (H2) which states that Liquidity, Leverage, Profitability and Business risk simultaneously affect the decision of expansion of Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX). Liquidity variable that has a dominant effect. R square shows a value of 0.481 has a contribution of 48.1% meaning that it has a strong enough influence on the dependent variable (expansion decision) and the remaining 51.9% is influenced by variables not examined in the study.